6H-Benzo[4, 5]thieno[2, 3-b]indole as a novel donor for efficient thermally activated delayed fluorescence emitters with EQEs over 20%. Issue 44 (30th October 2019) - Konidena, Rajendra Kumar; Lee, Kyung Hyung; Lee, Jun Yeob
Abstract : In this report, we developed two novel indole-based electron donors, 6 H -benzo[4, 5]thieno[2, 3- b ]indole (synBTI ) and 6 H -benzofuro[2, 3- b ]indole (synBFI ), for designing green thermally activated delayed fluorescence (TADF) emitters. Abstract : In this report, we developed two novel indole-based electron donors, 6 H -benzo[4, 5]thieno[2, 3- b ]indole (synBTI ) and 6 H -benzofuro[2, 3- b ]indole (synBFI ), for designing green thermally activated delayed fluorescence (TADF) emitters. Two TADF emitters, 2-(6 H -benzo[4, 5]thieno[2, 3- b ]indol-6-yl)-5-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)benzonitrile (BTITrz ) and 2-(6 H -benzofuro[2, 3- b ]indol-6-yl)-5-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)benzonitrile (BFITrz ), were synthesized by integrating the two new donors with an aryltriazine acceptor. The effects of the heteroatoms in the donor units on the photophysical and electroluminescence properties of the TADF emitters were investigated in detail. The photophysical analysis revealed that BTITrz showed a relatively small singlet–triplet energy splitting, short delayed fluorescence lifetime and high photoluminescence quantum yield (PLQY) compared to its congener BFITrz . As a result, the organic light emitting diode fabricated using the BTITrz emitter exhibited superior device performance with a maximum external quantum efficiency (EQE) of 20.7% and current efficiency (CE) of 63.6 cd A −1 . These results suggest that synBTI can function as a potential donor for designing efficient TADF emitters.